Detection of Anti-Lactoferrin and Anti-Lysozyme in Ulcerative Colitis Patients - Mohammed, Abbas Jassim (Diyala Journal of Medicine, 2019)
Background: Ulcerative colitis is an autoimmune inflammatory disease. Perinuclear anti-neutrophil cytoplasmic antibodies have been described in patients with inflammatory bowel disease, mainly ulcerative colitis, their role in pathogenesis and diagnostic value are still contentious. Objective: This study targeted at evaluating the incidence of auto antibodies against lactoferrin and lysozyme which belongs to perinuclear antineutrophil cytoplasmic antibodies and measurement the levels of C-reactive protein ,Study the relationship between anti-lactorferrin and anti-lysozyme antibodies , Study the association between anti-lactorferrin, anti-lysozyme antibodies and C-reactive protein concentration among ulcerative colitis patients. Patients and Methods: Fifty patients with ulcerative colitis be present at Al-Kadhimiya Teaching Hospital in Baghdad-Iraq and 25 healthy subjects were selected as the control group. Enzyme linked immune sorbent assay technique was used to detect the anti-lactoferrin and lysozyme antibody in sera of patients and healthy control groups and C- reactive protein was measured by qualitative and semi quantitative agglutination methods. Results: The results of study have showed the male were more affected with UC than female with ratio (1.2:1). The study showed statistically important variances for anti-lactoferrin and lysozyme antibodies between patients and control groups. The present study shown that the (30%) and (38%) of ulcerative colitis patients were seropositive for anti-lactoferrin and lysozyme antibodies, respectively. Conclusion: The prevalence of anti-lactoferrin and anti-lysozyme antibodies were similar to that reported in previous studies and their presence was associated with severity of ulcerative colitis .